Բանաձևային բանահյուսության որոշ ժանրերի առանձնահատկությունները Արցախի բանահյուսության մեջ - Սարգսյան, Արմեն (ԱրՊՀ հրատ․)
В статье представлены жанровые и смысловые особенности некоторых жанров арцахского формульного фольклора – пословиц-поговорок, анафем, благослoвлений, загадок, прозвищ сёл; а также приводятся соответствующие примеры. The article represents genre and semantic peculiarities of some genres of Artsakh formular folklore – proverbs and sayings, curses, blessings, enigmas, village nicknames. There are also corresponding examples in the article․
Keywords: Բանահյուսություն; Արցախ